EVALUATING THE THERAPEUTIC POTENTIAL OF Cuscuta reflexa AND Saussurea lappa IN THE MANAGEMENT OF MELASMA: A SINGLE BLIND RANDOMIZED CLINICAL TRIAL (Applied Biological Research, 2026)
To scientifically validate the drugs traditionally used by Arab and Greek physicians, a single blind, randomized, standard-controlled clinical trial was conducted on 36 melasma patients aged 15-50 years, with treatment duration of 60 days. The study aimed to evaluate the efficacy of a test drug formulation comprising of a decoction of Cuscuta reflexa and a paste of Sausserea lappa (mixed with honey), compared to the recommended allopathic treatment (standard control). The test group received a decoction of C. reflexa (5 g orally, once a day) along with topical application of S. lappa paste on the affected area for 15 min once a day. The control group was orally administered with tranxemic acid tablets (250 mg, twice daily) and topical azelaic acid (10%) on the affected area. The test group exhibited significant improvement in subjective parameters with significant decrease in the severity of hyper pigmentation. Both the groups showed significant improvement in objective parameters including melasma area and severity index (MASI) scores, by the 60th day of treatment (p < 0.001). The test drugs demonstrated noticeable therapeutic effects on both subjective and objective parameters, without any adverse effect. No significant difference was observed between test and standard control treatment.
Keywords: Cuscuta reflexa, decoction, hyperpigmentation, melasma, Saussurea lappa